2019
DOI: 10.1111/echo.14559
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging of a left atrial calcified amorphous tumor

Abstract: A cardiac calcified amorphous tumor (CAT) is an extremely rare non‐neoplastic cardiac mass composed of calcium nodules in an amorphous background of fibrin materials. Herein, we report a case of CAT in the left atrium of an asymptomatic 72‐year‐old man who underwent multimodality imaging and successful resection of the CAT. Results of the present case suggest that multimodality imaging plays an important role in detecting cardiac CAT, determining the treatment plan and serial follow‐ups for the patients after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…A CCAT is characterized by a calcified nodule in an amorphous background with fibrous degeneration and focal inflammation ( 3 ). Solely calcified cardiac mass without thrombus or inflammation are extremely rare ( 4 ). A past study showed that inflammation does not occur in CCATs in non-ESRD ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CCAT is characterized by a calcified nodule in an amorphous background with fibrous degeneration and focal inflammation ( 3 ). Solely calcified cardiac mass without thrombus or inflammation are extremely rare ( 4 ). A past study showed that inflammation does not occur in CCATs in non-ESRD ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate screening imaging modalities for cardiac mass include echocardiography, computed tomography (CT), cMRI, and PET-CT; they can be used to make differential diagnoses among myxomas, fibroelastomas, thrombi, and among others. All of these can eliminate the problem of differential diagnoses ( 4 ). Although PET-CT and FDG uptake can provide valuable information about inflammation for the differential diagnoses ( 5 ), histopathology is still needed to make a final diagnosis, especially for CCATs.…”
Section: Discussionmentioning
confidence: 99%